The effect of increasing lifespan and recycling rate on carbon storage in wood products from theoretical model to application for the European wood sector - Brunet-Navarro, Pau; Jochheim, Hubert; Muys, Bart (Mitigation and adaptation strategies for global change, 2017)
The use of wood products is often promoted as a climate change mitigation option to reduce atmospheric carbon dioxide concentrations. In previous literature, we identified longevity and recycling rate as two determining factors that influence the carbon stock in wood products, but no studies have predicted the effect of improved wood use on carbon storage over time. In this study, we aimed at evaluating changes in the lifespan and the recycling rate as two options for enhancing carbon stock in wood products for different time horizons. We first explored the behaviour over time of both factors in a theoretical simulation, and then calculated their effect for the European wood sector of the future. The theoretical simulation shows that the carbon stock in wood products increases linearly when increasing the average lifespan of wood products and exponentially when improving the recycling rate. The emissions savings under the current use of wood products in Europe in 2030 were estimated at 57.65 Mt carbon dioxide (CO 2 ) per year. This amount could be increased 5 Mt CO 2 if average lifespan increased 19.54 % or if recycling rate increased 20.92 % in 2017. However, the combination of both strategies could increase the emissions saving almost 5 Mt CO 2 more by 2030. Incrementing recycling rate of paper and paperboard is the best short-term strategy (2030) to reduce emissions, but elongating average lifespan of wood-based panels is a better strategy for longer term periods (2046).